18F-Labeled FAUC 346 and BP 897 Derivatives as Subtype-Selective Potential PET Radioligands for the Dopamine D3 Receptor - Hocke, Carsten; Prante, Olaf; Salama, Ismael; Hübner, Harald; Löber, Stefan; Kuwert, Torsten; Gmeiner, Peter (ChemMedChem, 2008)
Disturbances of neutrotransmission at the dopamine D3 receptor are related to several neuropsychiatric diseases and in particular to drug addiction. Herein, we report the computer-assisted prediction of D3 selectivities of new fluoroalkoxy-substituted receptor ligands by means of 3D-QSAR analysis. As close analogues of the D3-selective lead compound FAUC 346 and BP 879, the 19F-substituted test compounds 4a-d were synthesized and evaluated. In vitro investigation of their binding characteristics in transfected Chinese Hamster Ovary (CHO) cells led to excellent Ki values between 0.12 and 0.69 nm at the dopamine D3 subtype. The benzothiophene-substituted carboxamide 4a (K i=0.12 nm) displayed 133 and 283-fold selectivity over the structurally related D2Long and D4 subtypes, respectively. Mitogenesis assays showed the behavior of partial agonists. Based on these data, we synthesized the [18F]fluoroethoxy-substituted radioligands [ 18F]4a-d. The N-[4-[4-(2-hydroxyphenyl)piperazin-1-yl]butyl]-2- carboxamides 3a-d were prepared and labeled with 2-[18F] fluoroethyltosylate in a two-step procedure. Optimization of the 18F-labeling conditions led to radiochemical yields between 24 and 65 %. © 2008 Wiley-VCH Verlag GmbH & Co. KGaA.
UnivIS-Import:2015-04-14:Pub.2008.nat.dchph.lphch.18flab
Keywords: D3 receptor; Positron emission tomography; Radioligands